Bioethics and Universal Vulnerability: Exploring the Ethics and Practices of Research Participation. (17th September 2019) - Ries, Nola M; Thomson, Michael
Abstract: In this article, we advocate the adoption of universal vulnerability as a core value in bioethics. We argue that understanding vulnerability as the universal human condition—and rejecting the labelling of particular individuals or groups as vulnerable—would benefit bioethics and the research it governs. Bioethics first engaged with vulnerability in the context of participation in research and this continues to define how the value is typically understood. Thus, vulnerability is generally deployed to describe individuals (or populations), where real or perceived deficiencies limit the ability to function and to protect themselves from risks. Revisiting this initial context and the participation in research of people living with dementia, we note that the bioethical position of excluding the 'vulnerable' from research has led to major gaps in evidence and knowledge to inform care and support. Turning to universal vulnerability, we consider the research design and practices that the approach would mandate. We emphasise the importance of inclusive design and mechanisms of institutional support that enable participation. We argue that these positively impact on the scientific value of research and address social justice concerns around social inclusion. Our aim is to provoke a fundamental reassessment of how vulnerability is conceived of in bioethics.